Taylor Dome Ice Core Data - Steig, Eric J.; White, James (IEDA: US Antarctic Program Data Center, 2003)
The collection site is Taylor Dome, an ice-accumulation area on the East Antarctic ice sheet. The dome is a ridge about 20 x 80 km, which lies inland of the Transantarctic Mountains. Deep drilling by the Polar Ice Coring Office (PICO) at Taylor Dome reached bedrock at a depth of 554 meters during the 1993-1994 austral summer season. This data set includes mesurements of: beryllium-10 (betd.txt) oxygen isotopes (hi18o_td.txt and lo18o_td.txt) deuterium isotopes (deld_20cm.txt and deld_td.txt). These data were produced at the University of Washington from samples obtained in the field and via the University of New Hampshire automatic melting system. For beryllium, deuterium, and 20-cm oxygen isotope data, the st9810 ice age (kyB1950) timescale is used. For 0.5- to 1-m oxygen isotope data, the st9507 is used.